2019
DOI: 10.1002/qua.26127
|View full text |Cite
|
Sign up to set email alerts
|

Solvation effect on the vertical ionization energy of adenine‐thymine base pair: From microhydration to bulk

Abstract: In the present work, we investigate the effect of aqueous environment on the vertical ionization potential (VIP) of adenine-thymine (AT) base pair using a multilayer equation of the motion-coupled cluster method. The microsolvation can cause both blue-shift and red-shit of the IP values. However, the bulk water environment always results in the red-shift of the vertical ionization potential. Our study shows that the correct treatment of the short-range interaction plays an essential role in determining the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The first 55 snapshots are selected out of the original 400 snapshots using an energy-based prescreening scheme. 59,60 The instantaneous average VDE of these 55 snapshots is 8.29 eV, which is in good agreement with the original instantaneous average VDE of 8.24 eV. In the next step, we increased the number of water molecules included in the EA-EOM-DLPNO- CCSD-based QM/MM calculations in a shellwise manner for these 55 snapshots.…”
Section: Computational Detailssupporting
confidence: 70%
See 1 more Smart Citation
“…The first 55 snapshots are selected out of the original 400 snapshots using an energy-based prescreening scheme. 59,60 The instantaneous average VDE of these 55 snapshots is 8.29 eV, which is in good agreement with the original instantaneous average VDE of 8.24 eV. In the next step, we increased the number of water molecules included in the EA-EOM-DLPNO- CCSD-based QM/MM calculations in a shellwise manner for these 55 snapshots.…”
Section: Computational Detailssupporting
confidence: 70%
“…To further understand the distance dependence of the stabilizing effect provided by water, we have studied the effect of the size of the water environment on the calculated VDE values. First 55 snapshots are selected out of the original 400 snapshots using an energy-based pre-screening scheme 59,60 . The average VDE of these 55 snapshots is 8.29 eV, which is in good agreement with the original average value of 8.24 eV.…”
Section: Bulk-solvationmentioning
confidence: 99%
“…To have a quantitative understanding of the dependence of VDE values on the number of water molecules, we have checked the convergence of the VDE with respect to the number of solvation shells. We have first prescreened 42 snapshots using energy‐based criteria . We have chosen only those snapshots whose VDE values are within 0.65 eV of the average VDE of the original 400 snapshots.…”
Section: Resultsmentioning
confidence: 99%
“…Biased Sampling Using the VDE as the Parameter. Previous studies 35,86 on the ionization potential of solvated molecules have shown that biased sampling can be used as a handy tool to reduce the computational cost and time. In this study, a biased sampling was performed on the 400 snapshots generated in the previous step from the QM/MM dynamics.…”
Section: Calculation Of Electron Affinitymentioning
confidence: 99%